2022
DOI: 10.2196/35079
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Acceptability of a Brief Type 2 Diabetes Visual Animation: Mixed Methods Feasibility Study

Abstract: Background Visualizations of illness and treatment processes are promising interventions for changing unhelpful perceptions and improving health outcomes. However, these are yet to be tested in patients with type 2 diabetes mellitus (T2DM). Objective This study assesses the cross-cultural acceptability and potential effectiveness of a brief visual animation of T2DM at changing unhelpful illness and treatment perceptions and self-efficacy among patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Specific strategies to enhance effective PA teaching should be considered. Role modeling has been described as a modifiable variable for enhancing exercise self-efficacy [ 48 ]. Potentially, learning can be improved by encouraging visualisation, followed by repetition of the modelled behavior [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific strategies to enhance effective PA teaching should be considered. Role modeling has been described as a modifiable variable for enhancing exercise self-efficacy [ 48 ]. Potentially, learning can be improved by encouraging visualisation, followed by repetition of the modelled behavior [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Role modeling has been described as a modifiable variable for enhancing exercise self-efficacy [ 48 ]. Potentially, learning can be improved by encouraging visualisation, followed by repetition of the modelled behavior [ 48 ]. This highlights the importance of building strong patient-provider relationships and incorporating supportive communication strategies into healthcare practice.…”
Section: Discussionmentioning
confidence: 99%
“…27 A recent feasibility study found that a short diabetes visual animation was well received by patients in New Zealand, and future research could further develop this. 28 For Māori, interventions should include establishing trust, connection (whanaungatanga) and respect (manaakitanga) with the patient, as well as fostering empowerment (rangatiratanga). The presence of cultural support and/ or family (whānau) in consultations with Māori patients is also important.…”
Section: Discussionmentioning
confidence: 99%